High-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane and preparation method thereof

By introducing trifluoromethyl groups into polyimide precursor materials and adjusting the framework structure, a high-performance carbon molecular sieve hollow fiber membrane was prepared, which solved the problem of low permeability and achieved a high-permeability ethylene-ethane separation effect, meeting industrial needs.

CN121016516APending Publication Date: 2025-11-28DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511232948.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing hollow fiber membranes made of ethylene ethane carbon molecular sieves have shortcomings in separation performance, especially in terms of low permeability, which makes it difficult to meet the needs of industrial applications.

Method used

By adjusting the structure of the polyimide precursor material, introducing a large-volume trifluoromethyl group as a leaving group, and adjusting the tortuosity of the polymer skeleton, a high-performance carbon molecular sieve hollow fiber membrane is prepared by phase inversion method. The specific steps include chemical imidization and high-temperature carbonization treatment.

Benefits of technology

It significantly improves the permeability of hollow fiber membranes in carbon molecular sieves, greatly enhancing the industrial application potential of ethylene-ethane separation. The permeability can reach 27.8-346 GPU, meeting the requirements for distillation coupling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016516A_ABST
    Figure CN121016516A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of membrane preparation and application, and discloses a high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane and a preparation method thereof. The preparation method comprises the following steps: firstly, synthesizing a CF3-containing polyimide precursor material by adopting a chemical imidization method, applying the polyimide precursor to hollow fiber membrane spinning, and carbonizing the prepared hollow fiber membrane under a certain heating procedure to obtain the high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane. Compared with the existing ethylene and ethane separation carbon molecular sieve hollow fiber membrane, the carbon molecular sieve hollow fiber membrane prepared by the invention has the advantages that the C2H4 / C2H6 separation performance is obviously improved, and the industrial application prospect is better.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of membrane preparation and application, and discloses a high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane and a preparation method thereof. BACKGROUND

[0002] Olefin / alkane separation is recognized as one of the seven chemical separations that can change the world. Due to the close boiling points of ethylene and ethane, the energy consumption of low-temperature rectification and other methods is huge. Membrane separation has the advantages of low energy consumption, simple operation, flexible equipment, etc., and is a potential future technology. From flat membranes to hollow fiber membranes is an important step in the industrialization of membrane materials. Hollow fiber membranes have the advantages of self-supporting structure and high packing rate, and the prepared membrane separation device has high surface area per unit volume, small equipment volume and wide application scenarios. However, the separation selectivity and permeation rate of traditional polymer hollow fiber membranes for ethylene and ethane are low. Carbon membranes have better separation performance than polymer membranes, and the prepared carbon molecular sieve hollow fiber membranes have higher gas permeation rate at the same selectivity and high chemical stability, which are the preferred membrane materials for ethylene and ethane separation.

[0003] Currently reported ethylene-ethane separation carbon molecular sieve hollow fiber membrane materials include PIM-1 and Matrimid. PIM-1 is prone to defects during carbonization due to its high material rigidity and thin skin layer of polymer PIM-1 hollow fiber membrane. The rigidity of Matrimid and other polyimide materials is reduced, which is more conducive to carbonization. However, the molecular chains of Matrimid material are closely packed, and the space between carbon chains is small during carbonization, so that the carbon molecular sieve membrane has poor intrinsic gas separation performance due to low permeation rate. The prepared carbon molecular sieve hollow fiber membrane has a selectivity of 6.0 and a permeation rate of only 1.4 GPU (Xu L, Rungta M, Koros W J. Matrimid derived carbon molecular sieve hollow fiber membranes for ethylene / ethane separation[J]. Journal of membrane science, 2011, 380(1-2): 138-147.).

[0004] With reference to the idea that the permeability of the corresponding carbon molecular sieve flat membrane can be adjusted by adjusting the polymer backbone structure or introducing groups easy to be removed during carbonization on the main chain structure, the application introduces a bulky trifluoromethyl (-CF3) as a leaving group on the dianhydride structure, and a simple diamine structure is used to adjust the tortuosity of the polymer backbone, so as to adjust the pore size and pore size distribution between carbon chains during carbonization, so that the ethylene-ethane intrinsic separation performance is optimized, and the hollow fiber membrane is prepared by a phase inversion method, and the ethylene-ethane separation carbon molecular sieve hollow fiber membrane with high permeability is formed by carbonization under a certain carbonization program. SUMMARY

[0005] In order to solve the problem of insufficient separation performance of the existing ethylene-ethane carbon molecular sieve hollow fiber membrane, the application provides a high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane and a preparation method thereof by adjusting the structure of a polyimide precursor material.

[0006] The technical scheme of the application is as follows:

[0007] A high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane contains the following repeat unit structure:

[0008] ;

[0009] Wherein, m and n represent the molar ratio of different polymer units, m:n = 0.1-10:1;

[0010] Ar1 is one of the following diamine structures:

[0011] 、 、 、

[0012] 、 、 ;

[0013] Ar2 is one of the following dianhydride structures:

[0014] 、 、

[0015] .

[0016] A preparation method of a high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane, the high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane is prepared by a chemical imidization method; first, a polyimide precursor material is synthesized, the polyimide precursor is used for hollow fiber membrane spinning, and the prepared hollow fiber membrane is carbonized under a certain temperature rising program, to obtain a high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane;

[0017] The steps are as follows:

[0018] (1) Preparation of the -CF3 group-containing polyimide polymer: under a nitrogen atmosphere, the diamine monomer Ar1 is dissolved in NMP, after the diamine monomer Ar1 is completely dissolved, an ice water bath is used to keep the solution at 0°C, then the dianhydride monomer Ar2 is added, the molar ratio of the diamine monomer Ar1 and the dianhydride monomer Ar2 is controlled to be 1:1, a reaction solution with a total mass fraction of 10-30wt% is prepared, stirring is carried out for 1-5h, the ice water bath is removed and the reaction is continued at room temperature for 12-24h, then a dehydrating agent and a catalyst are added to carry out chemical imidization for 12-24h; after the reaction is completed, the solution is poured into methanol for washing three times, each time after washing, filtration is carried out, after washing three times, the polymer is dried to obtain the -CF3 group-containing polyimide polymer;

[0019] (2) Preparation of the polyimide polymer hollow fiber membrane: the -CF3 group-containing polyimide polymer obtained in step (1) is dissolved in a solvent to prepare a spinning casting solution with a certain concentration; the solvent is mixed with water to prepare a core liquid; a dry-jet wet spinning process is adopted, the casting solution is heated to a certain temperature, the extrusion rate of the casting solution and the core liquid, the air gap height, the gel bath temperature, and the take-up speed are adjusted, and the polyimide polymer hollow fiber membrane is spun; after spinning, the membrane is cleaned, solvent exchange is carried out, and drying is carried out to obtain the polyimide polymer hollow fiber membrane;

[0020] (3) Preparation of the carbon molecular sieve hollow fiber membrane: under a nitrogen atmosphere, the polyimide polymer hollow fiber membrane obtained in step (2) is subjected to high-temperature carbonization treatment, after the carbonization is completed, natural cooling to room temperature is carried out, and the carbon molecular sieve hollow fiber membrane is obtained.

[0021] In the above method, in step (1):

[0022] The dehydrating agent is acetic anhydride;

[0023] The catalyst is one of pyridine and trimethylpyridine;

[0024] The molar ratio of the dehydrating agent and the diamine monomer is 5:1-1:1;

[0025] The molar ratio of the catalyst and the dehydrating agent is 20:1-5:1.

[0026] In step (2):

[0027] The solvent includes one or two or more of the following: non-volatile solvents (NMP, DMAc, DMF), volatile solvents (THF, CHCl3), non-solvents (EtOH, MeOH, H2O), and inorganic salts (LiNO3, LiCl, KNO3, KCl);

[0028] The polymer concentration in the spinning casting solution is 10-40wt%;

[0029] The solvent in the core solution is one of NMP, DMAc, DMF or a mixture of two;

[0030] The mass percentage of water in the core solution is 0-50wt%;

[0031] The temperature range of the casting solution heated to is 30-80℃;

[0032] The extrusion rate of the casting solution is 120-720mL / h, and the extrusion rate ratio of the casting solution and the core solution is 5:1-1:1;

[0033] The air gap height is 5-30cm;

[0034] The gel bath temperature is 20-70℃;

[0035] The take-up speed is 20-100m / min;

[0036] The solvent used for cleaning is one of water, methanol and ethanol, and the washing times are 3-6 times, and the washing time of each time is 12h;

[0037] The reagent used for solvent exchange is one or more than two mixed of methanol, ethanol and n-hexane, and the solvent exchange times are 2-5 times;

[0038] The drying temperature is 120-200℃, and the drying time is 8-12h.

[0039] The carbonization temperature in step (3) is 500-900℃, and the carbonization time is 1-3h.

[0040] The outer diameter size of the polymer hollow fiber membrane prepared by the application is 200-400μm, and the wall thickness is 40-100μm; the outer diameter size of the carbon molecular sieve hollow fiber membrane prepared by the application is 100-300μm, and the wall thickness is 20-70μm.

[0041] The beneficial effects of the application are that: compared with other ethylene-ethane separation carbon molecular hollow fiber membranes, the application adjusts the structure of the polyimide precursor material to prepare a high-performance carbon molecular sieve membrane with higher permeability, spins the material and carbonizes to prepare a carbon molecular sieve hollow fiber membrane with a higher upper limit of permeability, which greatly improves the possibility of industrial application of ethylene-ethane separation membrane. BRIEF DESCRIPTION OF DRAWINGS

[0042] Figure 1 The SEM diagram of the cross section of the carbon molecular sieve hollow fiber membrane prepared in Example 1 of the application;

[0043] Figure 2 This is a magnified SEM image of a cross-section of the carbon molecular sieve hollow fiber membrane prepared in Example 1 of the present invention. Detailed Implementation

[0044] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.

[0045] Example 1

[0046] Under a nitrogen atmosphere, 7.303 g of m-phenylenediamine (MPD) was dissolved in approximately 150 mL of NMP. After the MPD was completely dissolved, an ice-water bath was added to maintain the solution at 0 °C. Then, 30 g of 6 FDA (molar ratio 1:1) was added, and the reaction was carried out for 3 h with stirring at approximately 200 rpm. The ice-water bath was removed, and the reaction was continued at room temperature for 24 h. Subsequently, 50 mL of acetic anhydride and 5 mL of pyridine catalyst were added for chemical imidization, and the reaction was allowed to proceed for 24 h. After the reaction was complete, the solution was washed three times, each time in 1000 mL of methanol for 24 h, and then filtered. After washing, the polymer was dried in an oven at 210 °C for 12 h to achieve complete imidization, yielding a polyimide polymer containing -CF3 groups.

[0047] A casting solution was prepared using a 20 wt% concentration of the obtained -CF3 group-containing polyimide polymer, 45 wt% NMP, 17 wt% methanol, 15 wt% tetrahydrofuran, and 3 wt% lithium nitrate. A dry-jet wet spinning process was employed. The casting solution was heated to 60°C, the extrusion rate was 180 mL / h, the core solution extrusion rate was 60 mL / h, the air gap height was 30 cm, the NMP / H2O volume ratio was 80:20, the gel bath temperature was 50°C, and the take-up rate was 20 m / min for hollow fiber membrane spinning. After spinning, the membrane fibers were washed with water for 3 days and subjected to solvent exchange three times each with methanol and n-hexane. The membrane was then dried at 120°C for 12 h to obtain a polymer hollow fiber membrane with an outer diameter of 320 μm and a wall thickness of 70 μm. The obtained polymer hollow fiber membrane was placed in a three-section tube furnace and carbonized at 550°C for 2 hours under a nitrogen atmosphere. After carbonization, it was naturally cooled to room temperature to obtain a carbon molecular sieve hollow fiber membrane with an outer diameter of 140 μm and a wall thickness of 30 μm.

[0048] The gas separation performance was tested using the constant pressure variable volume method, with a test temperature of 35℃ and a test pressure difference of 0.2MPa.

[0049] Comparative Example 1

[0050] A casting solution was prepared using 20 wt% Matrimid polymer, 45 wt% NMP, 17 wt% methanol, 15 wt% tetrahydrofuran, and 3 wt% lithium nitrate. A dry-jet wet spinning process was employed. The casting solution was heated to 60°C, the extrusion rate was 180 mL / h, the core solution extrusion rate was 60 mL / h, the air gap height was 30 cm, the NMP / H2O volume ratio was 80:20, the gel bath temperature was 50°C, and the take-up rate was 20 m / min. Hollow fiber membranes were then spun. After spinning, the membrane fibers were washed with water for 3 days and subjected to solvent exchange three times each with methanol and n-hexane. The membranes were then dried at 120°C for 12 h to obtain a polymer hollow fiber membrane with an outer diameter of 320 μm and a wall thickness of 80 μm. The obtained polymer hollow fiber membrane was placed in a three-section tube furnace and carbonized at 550°C for 2 hours under a nitrogen atmosphere. After carbonization, it was naturally cooled to room temperature to obtain a carbon molecular sieve hollow fiber membrane with an outer diameter of 160 μm and a wall thickness of 40 μm.

[0051] Comparative Example 2

[0052] Under a nitrogen atmosphere, 7.303 g of m-phenylenediamine (MPD) was dissolved in approximately 150 mL of NMP. After the MPD was completely dissolved, an ice-water bath was added to maintain the solution at 0 °C. Then, 30 g of 6 FDA (molar ratio 1:1) was added, and the reaction was carried out for 3 h with stirring at approximately 200 rpm. The ice-water bath was removed, and the reaction was continued at room temperature for 24 h. Subsequently, 50 mL of acetic anhydride and 5 mL of pyridine catalyst were added for chemical imidization, and the reaction was allowed to proceed for 24 h. After the reaction was complete, the solution was washed three times, each time in 1000 mL of methanol for 24 h, and then filtered. After washing, the polymer was dried in an oven at 210 °C for 12 h to achieve complete imidization, yielding a polyimide polymer containing -CF3 groups.

[0053] A casting solution was prepared using a 20 wt% concentration of the obtained -CF3 group-containing polyimide polymer, 45 wt% NMP, 17 wt% methanol, 15 wt% tetrahydrofuran, and 3 wt% lithium nitrate. A dry-jet wet spinning process was employed. The casting solution was heated to 60°C, the extrusion rate was 180 mL / h, the core solution extrusion rate was 60 mL / h, the air gap height was 30 cm, the NMP / H2O volume ratio was 80:20, the gel bath temperature was 50°C, and the take-up rate was 20 m / min for hollow fiber membrane spinning. After spinning, the membrane fibers were washed with water for 3 days and subjected to solvent exchange three times each with methanol and n-hexane. The membrane was then dried at 120°C for 12 h to obtain a polymer hollow fiber membrane with an outer diameter of 320 μm and a wall thickness of 70 μm.

[0054] Example 2

[0055] Based on Example 1, the carbonization temperature was changed from 550℃ to 675℃ to obtain a carbon molecular sieve hollow fiber membrane with an outer diameter of 135μm and a wall thickness of 28μm.

[0056] Example 3

[0057] Based on Example 1, the carbonization temperature was changed from 550℃ to 700℃ to obtain a carbon molecular sieve hollow fiber membrane with an outer diameter of 133μm and a wall thickness of 27μm.

[0058] Example 4

[0059] Based on Example 1, the casting solution was prepared by replacing the composition of the obtained polyimide polymer containing -CF3 groups at a concentration of 29 wt%, 42 wt% NMP, 16 wt% methanol, 10 wt% tetrahydrofuran, and 3 wt% lithium nitrate. The air gap height was changed from 30 cm to 20 cm, and the carbonization temperature remained at 550 °C, resulting in a carbon molecular sieve hollow fiber membrane with an outer diameter of 140 μm and a wall thickness of 40 μm.

[0060] Example 5

[0061] Based on Example 1, the casting solution was prepared by replacing the composition of the obtained polyimide polymer containing -CF3 groups at a concentration of 29 wt%, NMP at 42 wt%, methanol at 16 wt%, tetrahydrofuran at 10 wt%, and lithium nitrate at 3 wt%. The air gap height was replaced from 30 cm to 20 cm, and the carbonization temperature was replaced from 550 °C to 675 °C, resulting in a carbon molecular sieve hollow fiber membrane with an outer diameter of 135 μm and a wall thickness of 35 μm.

[0062] Example 6

[0063] Based on Example 1, the dehydrating agent acetic anhydride was replaced from 50 mL to 100 mL, and the catalyst was replaced from 5 mL pyridine to 5 mL trimethylpyridine for chemical imidization.

[0064] Example 7

[0065] Based on Example 1, the catalyst was replaced with 10 mL of pyridine instead of 5 mL of pyridine for chemical imidization.

[0066] Example 8

[0067] Based on Example 1, the casting solution composition was changed to 10 wt% of the obtained polyimide containing -CF3 groups, 61 wt% DMF, 16 wt% ethanol, 10 wt% chloroform, and 3 wt% potassium nitrate. The air gap height was changed from 30 cm to 5 cm. The casting solution heating temperature was changed from 60 °C to 30 °C.

[0068] Example 9

[0069] Based on Example 1, the casting solution composition was changed to 40 wt% of the obtained polyimide polymer containing -CF3 groups, 31 wt% DMF, 16 wt% ethanol, 10 wt% chloroform, and 3 wt% potassium nitrate. The casting solution extrusion rate was changed from 180 mL / h to 720 mL / h, the core solution extrusion rate was changed from 60 mL / h to 150 mL / h, the core solution NMP / H2O volume ratio was changed from 80:20 to 50:50, the gel bath temperature was changed from 50℃ to 20℃, and the take-up rate was changed from 20 m / min to 100 m / min.

[0070] Example 10

[0071] Based on Example 1, the casting solution composition was changed to 40 wt% of the obtained polyimide polymer containing -CF3 groups, 31 wt% DMAc, 16 wt% water, 10 wt% chloroform, and 3 wt% lithium chloride. The core liquid extrusion rate was changed from 60 mL / h to 180 mL / h, the gel bath temperature was changed from 50°C to 70°C, and the filament take-up rate was changed from 20 m / min to 60 m / min.

[0072] Table 1. Ethylene / ethane permeability and selectivity of carbon molecular sieve hollow fiber membranes prepared in the comparative and example cases.

[0073]

[0074] The gas separation performance test results are shown in Table 1. In Comparative Example 1, the carbon molecular sieve hollow fiber membrane prepared with Matrimid polymer showed a permeability of only 2.6 GPU for ethylene ethane, while in Comparative Example 2, the polyimide polymer hollow fiber membrane prepared without carbonization showed a permeability of only 0.85 GPU for ethylene ethane. However, the ethylene ethane separation carbon molecular sieve hollow fiber membrane provided by this invention exhibits significantly improved permeability for ethylene ethane, reaching a minimum of 27.8 GPU and a maximum of 346 GPU.

[0075] Studies have shown that when the permeability of an ethylene ethane separation membrane is >32 GPU, it can meet the conditions for coupling with distillation (RenY, Liang X, Dou H, et al. Membrane‐based olefin / paraffin separations[J].Advanced Science, 2020, 7(19): 2001398.). This invention prepares an ethylene ethane carbon molecular sieve hollow fiber membrane with high permeability through material structure design. Using this carbon molecular sieve hollow fiber membrane, combined with subsequent modification, makes it easier to meet industrial requirements.

Claims

1. A high-performance carbon molecular sieve hollow fiber membrane for ethylene-ethane separation, characterized in that, This high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane contains the following repeating unit structure: ; Where m and n represent the molar ratio of different polymer units, m:n = 0.1-10:1; Ar1 is one of the following diamine structures: 、 、 、 、 、 ; Ar2 is one of the following dianhydride structures: 、 、 。 2. The high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane according to claim 1, characterized in that, The high-performance ethylene ethane separation carbon molecular sieve hollow fiber membrane has an outer diameter of 200-400 μm and a wall thickness of 40-100 μm.

3. The high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane according to claim 1, characterized in that, The high-performance ethylene ethane separation carbon molecular sieve hollow fiber membrane has an outer diameter of 100-300 μm and a wall thickness of 20-70 μm.

4. A method for preparing a high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane, characterized in that, The steps are as follows: (1) Preparation of polyimide polymer containing -CF3 group: Under nitrogen atmosphere, diamine monomer Ar1 is dissolved in NMP. After the diamine monomer Ar1 is completely dissolved, an ice water bath is added to keep the solution at 0℃. Then, dianhydride monomer Ar2 is added, and the molar ratio of diamine monomer Ar1 to dianhydride monomer Ar2 is controlled to be 1:1 to prepare a reaction solution with a total mass fraction of 10-30wt%. The reaction is stirred for 1-5h. The ice water bath is removed and the reaction continues at room temperature for 12-24h. Then, a dehydrating agent and catalyst are added to carry out a chemical imidization reaction for 12-24h. After the reaction is completed, the solution is poured into methanol and washed three times. After each washing, the solution is filtered. After washing three times, the polymer is dried to obtain polyimide polymer containing -CF3 group. (2) Preparation of polyimide polymer hollow fiber membrane: The polyimide polymer containing -CF3 groups obtained in step (1) is dissolved in a solvent to prepare a spinning casting solution of a certain concentration; the solvent is mixed with water to prepare a core solution; the casting solution is heated to a certain temperature using a dry-jet wet spinning process, and the extrusion rate of the casting solution and the core solution, the air gap height, the gel bath temperature, and the take-up rate are adjusted to spin hollow fiber membrane; after spinning, the membrane fibers are cleaned, solvent exchanged, and dried to obtain a polyimide polymer hollow fiber membrane; (3) Preparation of carbon molecular sieve hollow fiber membrane: Under a nitrogen atmosphere, the polyimide polymer hollow fiber membrane obtained in step (2) is carbonized at high temperature. After carbonization, it is naturally cooled to room temperature to obtain carbon molecular sieve hollow fiber membrane.

5. The preparation method according to claim 4, characterized in that, In step (1): The dehydrating agent is acetic anhydride; The catalyst is one of pyridine and trimethylpyridine; The molar ratio of the dehydrating agent to the diamine monomer is 5:1 to 1:1; The molar ratio of the catalyst to the dehydrating agent is 20:1-5:

1.

6. The preparation method according to claim 4, characterized in that, In step (2): The solvent includes one or more of the following: non-volatile solvents, volatile solvents, non-solvents, and inorganic salts. The polymer concentration in the spinning casting solution is 10-40 wt%. The solvent in the core fluid is one or a mixture of two of NMP, DMAc, and DMF; The water content in the core fluid is 0-50 wt%; The casting solution is heated to a temperature range of 30-80℃; The extrusion rate of the casting solution is 120-720 ml / h, and the extrusion rate ratio of the casting solution to the core solution is 5:1-1:

1. The air gap height is 5-30cm; The gel bath temperature is 20-70℃; The winding rate is 20-100 m / min; The solvent used for cleaning is one of water, methanol, or ethanol. The number of washing cycles is 3-6, and each washing cycle lasts for 12 hours. The reagent used for solvent exchange is one or more of methanol, ethanol, and n-hexane, and the number of solvent exchanges is 2-5 times. The drying temperature is 120-200℃, and the drying time is 8-12 hours.

7. The method for preparing the high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane according to claim 6, characterized in that, The non-volatile solvent is NMP, DMAc, or DMF; the volatile solvent is THF or CHCl3; the non-solvent is EtOH, MeOH, or H2O; and the inorganic salt is LiNO3, LiCl, KNO3, or KCl.

8. The method for preparing the high-performance ethylene-ethane separation carbon molecular sieve hollow fiber membrane according to claim 4, characterized in that, In step (3): The carbonization temperature is 500-900℃, and the carbonization time is 1-3h.